A 3D Nanostructured Hydrogel‐Framework‐Derived High‐Performance Composite Polymer Lithium‐Ion Electrolyte. Issue 8 (16th January 2018) - Bae, Jiwoong; Li, Yutao; Zhang, Jun; Zhou, Xingyi; Zhao, Fei; Shi, Ye; Goodenough, John B.; Yu, Guihua
Abstract: Solid‐state electrolytes have emerged as a promising alternative to existing liquid electrolytes for next generation Li‐ion batteries for better safety and stability. Of various types of solid electrolytes, composite polymer electrolytes exhibit acceptable Li‐ion conductivity due to the interaction between nanofillers and polymer. Nevertheless, the agglomeration of nanofillers at high concentration has been a major obstacle for improving Li‐ion conductivity. In this study, we designed a three‐dimensional (3D) nanostructured hydrogel‐derived Li0.35 La0.55 TiO3 (LLTO) framework, which was used as a 3D nanofiller for high‐performance composite polymer Li‐ion electrolyte. The systematic percolation study revealed that the pre‐percolating structure of LLTO framework improved Li‐ion conductivity to 8.8×10 −5  S cm −1 at room temperature. Abstract : Path finder : The percolation effect on the conductivity of composite polymer electrolytes has been investigated. Typical nanoparticle fillers agglomerate at high concentrations, resulting in discontinuous lithium‐ion conducting pathways. A nanostructured hydrogel‐framework electrolyte exhibits much higher conductivity through a continuous interphase formed by a pre‐percolated network.